Clinical profile of Dengue infection at a center in north Karnataka, India - Adnan Imam; Prashanth ED (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2019)
Dengue is one of the most common arbovirus infection worldwide, which is a vector borne disease caused by the bite of Ades Aegypti mosquito. Symptoms of the infected individuals have a very broad range of presentation having similarities with other infections like malaria and influenza like illness etc. It is a retrospective study conducted at a centre in north Karnataka with the sampling method of quota or sequential sampling with inclusion of 121 cases all seropositive for dengue antigen or antibodies or both in the monsoon season from july 2018 till November 2018. The complete blood picture and liver enzymes like SGPT and SGOT were assessed during the period of the infected individuals. Leucopoenia is taken below 4000 cells/cumm, thrombocytopenia is taken below 100000 per cumm and liver enzymes were evaluated and graded as per the CTCAE guidelines version 4.0. The two tailed T Test was used to determine the significant change in the SGOT and SGPT liver enzymes. The symptoms ranged from mild to severe ones like fever, headache, nausea, vomiting, abdominal pain, generalised body ache (myalgia), cough, Rash, retro bulbar pain, bleeding, hypotension, signs of plasma leakage, leucopoenia, thrombocytopenia, SGOT (serum glutamic oxaloacetic transaminase) or AST (Aspartate aminotranferase) and SGPT (Serum glutamic pyruvic transaminase) or ALT (Alanine Transaminase), hypotension (blood pressure of 90/60 mm of Hg or lower), pleural effusion and ascites. 1.7% of the individual even showed seropositivity but didn't have any episode of fever and elevation of SGOT was significantly raised with respect to SGPT which was nearly within normal range for nearly half of the infected patients. This indicates that muscle injury is more significant with respect to the liver injury during the course of the disease. Negligible number of individual landed up in complications like Dengue Hemorrhagic fever or dengue shock syndrome if prompt and proper management of the disease is done. It was also seen that the affected individuals were more from the age group of 16 years to 37 years, the cause for which still need to be explained on a bigger population size.